Clinical Trends, Indications, Postoperative Complications of Hysterectomy Patients- A Retrospective Study (Global Journal of Medical Research, 2019)
Abstract not found
Keywords: hysterectomy; mumbai; clinical profile; fibroid; menorrhagia